(untitled) (Fiep Bulletin - online, 2015)
The wrestlings, games of opposition, sports of combat, exist since the beginning of the times in all the civilizations. Nowadays this context is part of curricular disciplines in university level which is seen as a pedagogical instrument in the formation of the child. The present study it has for objective to consider a reflection with respect to the practice of the fights in infancy, as well as ponctuates pedagogical principles that must be part of the formation of the involved professionals of Physical Education with the block of contents called fights. The methodology used was descriptive, based on a revision of literature with an emphasis in the National Curricular Parameters (PCN’ s). The Corporal Culture of the Movement considers a diversity of practical and cultural manifestations. It turned to this, some comments had been made in relation to the attitude objectives that must direct practical the pedagogical ones in the search of a paradigmatic change. Therefore, so that if the fights in the understood group age between 7 and 12 , can work, they are necessary to the search of a differentiated pedagogy, come back toward solution of problems, where the great victory will be the development of the pupil in the integral formation of the individual.